Bleeding Per Rectum: A Retrospective Study of 120 Cases - AL-Ubaide, Amer Fakhree; M. Al-Ani , Raid (AL-Kindy College Medical Journal, 2024)
Background: Lower gastrointestinal bleeding is one of the common problems seen worldwide, could be serious and occur at any age. Several studies conducted all over the world verified that there were variations in frequencies of etiologies of bleeding per rectum in their population, however, in the Middle East and Asia, the etiology of rectal bleeding differs from the West.Objectives: To assess the causes of bleeding per rectum and to find if there is an association between rectal bleeding and various variables.Subjects and methods: This was a retrospective cross-sectional study of 120 patients with bleeding per rectum for one year were studied in Al Ramadi Teaching Hospital, Ramadi City, Iraq. The patients underwent a full history and thorough physical examination. In all cases, initial digital rectal examination and proctoscopy were performed. Patients presented with a noticeable diagnosis of massive bleeding from the rectum were not included in our study.Results: There were 84 males (64%) with male to female ratio of 2.33: 1. The median age of patients was 38 years (age ranged from 15-81 years). The main age group was ≤ 50 years (n = 95, 79.2%).  The hemorrhoid was the most common cause of rectal bleeding (n = 95, 79.2%). The second cause was anal fissure which was found in 26 cases (21.65 %). Colorectal carcinoma was seen in 14 patients (11.67%), and most of them (n = 13) were above 50 years of age. There was no significant association between the rectal bleeding causes and the gender. However, there were highly significant differences between the causes and the age and bowel habits of the patients (P-value = 0.0001).Conclusion: Hemorrhoids were the most prevalent cause of rectal bleeding. The patient's age and bowel habit might be determined the cause of bleeding per rectum.